A territorialização da política de nucleação e o fechamento de escolas no campo em União dos Palmares/AL (2005-2015) - Silva, Edilma José da (2016)
The origin of Brazilian education is characterized by the oppression and exclusion of the ruling class on the working class, especially the one who works and lives in rural areas. This way, considering the educational policies we observe that they are engaged in the education for labor force in order to meet the country’s economic demands. The focus given to the labor force formation characterized the rural education guidelines. Contrasting what is proposed by the educational guidelines, the socioterritorial movements engaged in constructing proposals that present new possibilities of thinking education, based on the concept of education in rural areas. In the context of this disagreement between what is imposed by the State and the proposals of socioterritorials movements, this study aims to analyze the process of territorialization of the nucleation policy and the closure of rural schools in União dos Palmares/AL, between 2005 and 2015. In doing so, the study presents the history of territorial and educational formation in Alagoas. It discusses the process of organization of Brazilian education, emphasizing the development of educational public policies to the rural areas. It also presents a panorama of the education reality and identifies the government initiatives related to the territorialization of the nucleation policy of local schools, and analyzes the official statements from the managers of the studied schools. The policy analyzed in this paper arises with the intention of concentrating resources and rationalizing expenses, on the ground of educational quality improvement, founded on a neoliberal discourse that, in fact, means the precariousness and consequently the closuring of rural schools. The methodology applied in this study is founded between theory and practice and will consider the quantitative and qualitative nature of the research, highlighting the literary revisions about the studied subjects in addition to analyze the primary and secondary data to constitute a situational panorama of the studied object in the chosen town. The field research was conducted through semi-structured interviews in loco with local Education Department representatives in União dos Palmares – AL, managers, teachers and students’ parents from the studied schools.